Comparative study of radiation-induced luminescence properties in Eu:SrAl2O4 translucent ceramic and single crystal. (July 2019) - Nakauchi, Daisuke; Nakamura, Fumiya; Okada, Go; Kimura, Hiromi; Kawaguchi, Noriaki; Yanagida, Takayuki
Abstract: A Eu-doped SrAl2 O4 translucent ceramic was synthesized by the spark plasma sintering technique while a single crystal was grown by the floating zone method. Further, comparative studies of the scintillation and ionizing radiation-induced storage luminescence properties were performed. The transmittance of the synthesized ceramic is 60–70%, which is close to that of the single crystal. Both materials exhibit photoluminescence and scintillation predominantly with a broad emission peaking around 510 nm. The obtained decay time constants confirm that the major origin of the emission is the 5 d-4f transitions of Eu 2+, and the decay curve of the ceramic sample indicates the presence of the emission due to some kinds of defects. From the pulse height spectra measured under 137 Cs gamma-ray irradiation, the light yields of the single crystal and ceramic are 29, 000 and 5700 photons/MeV, respectively. As storage luminescence properties, thermoluminescence and afterglow properties were also evaluated. Highlights: A Eu-doped SrAl2 O4 translucent ceramic was successfully synthesized by the spark plasma sintering technique. Comparative studies of the radiation induced luminescence properties were performed. The synthesized Eu-doped SrAl2 O4 translucent ceramic shows the highest transmittance ever. There is a negative correlation between scintillation and storage luminescence properties.